Sentiment Analysis to Prediction DKI Jakarta Governor 2017 on Indonesian Twitter - Ghulam Asrofi Buntoro (Universitas Trunojoyo Madura, 2018)
This study was conducted to test opinion data tweet of three candidates for governor Jakarta, 2017. Data only in Indonesian tweet, data tweet 100 tweets with keywords AHY, 100 tweets with keywords Ahok, and 100 tweets with keywords Anies. Data taken by random either from a normal user or online media at Twitter. Indonesian tweet opinion with three candidates for governor Jakarta in 2017 divided into three sentiment: positive, neutral and negative. Preprocessing data is, Lower Case Tokens, Normalization, Tokenization, Cleansing and Filtering. Classification method in this study using Naïve Bayes classifier (NBC), because this method is the most widely performed for sentiment analysis and proven always produce highest accuracy. Results of classification, Precision AHY data scored the highest with 95% and 95% Recall, while Ahok data lowest Precision scores with 81.6% and 82% recall.